Islamic Education and Character Building in The 4.0 Industrial Revolution - Mohammad Adnan (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
This article describes the concept of Islamic education, in which case the emphasis is on the implementation of Islamic religious education. The implementation of Islamic religious education itself is an effort to instill the values ​​of Islamic aqeedah to every student as an effort to create a generation of Muslims who can and are able to live and believe in every truth in the teachings of Islam itself. This article uses a literature review method with content analysis design. Students are willing to practice the values ​​of Islamic teachings at any time, whenever, and wherever the teachings of Islam want to be conveyed are the problems of Islamic education should not be taken for granted so that Islamic education can compete and become educational goals that are achieved. The application of Islamic education in the industrial revolution 4.0 era is very important in developing the quality of children's potential, both in mastering science and technology as well as in terms of character, attitude and appreciation, and practice of religious teachings.